TIAR marks nuclear G2/M transition granules and restricts CDK1 activity under replication stress - Lafarga, Vanesa; Hörth, Katharina; Pauleau, Anne-Laure; Bruer, Marius; Erhardt, Sylvia; Stoecklin, Georg (EMBO reports, 2019)
Abstract The G2/M checkpoint coordinates DNA replication with mitosis and thereby prevents chromosome segregation in the presence of unreplicated or damaged DNA. Here, we show that the RNA-binding protein TIAR is essential for the G2/M checkpoint and that TIAR accumulates in nuclear foci in late G2 and prophase in cells suffering from replication stress. These foci, which we named G2/M transition granules (GMGs), occur at low levels in normally cycling cells and are strongly induced by replication stress. In addition to replication stress response proteins, GMGs contain factors involved in RNA metabolism as well as CDK1. Depletion of TIAR accelerates mitotic entry and leads to chromosomal instability in response to replication stress, in a manner that can be alleviated by the concomitant depletion of Cdc25B or inhibition of CDK1. Since TIAR retains CDK1 in GMGs and attenuates CDK1 activity, we propose that the assembly of GMGs may represent a so far unrecognized mechanism that contributes to the activation of the G2/M checkpoint in mammalian cells.